Monetarist arithmetic at COVID-19 time: a take on how not to misapply the quantity theory of money - Pinter, Julien Matthieu Albert (2021)
The COVID-19 crisis has revived an old heated debate on whether significant increases in the money supply - such as the ones seen after the pandemic outbreak - ultimately lead to higher inflation. Some observers have alluded to the quantity theory of money for that purpose, though in our view, this has sometimes been in a misleading way. Against this background, this paper seeks to clarify several aspects of the quantity theory of money and the so-called "monetarist" approach to it, which are useful to apply it fairly in the current world. First, we review and discuss the meaning of the velocity term in the quantity equation. We argue that it has no relevance as a behavioural concept: there is no such thing as a "desired velocity". Rather, income velocity should be seen as a variable deriving from a larger system of parameters and variables related to money demand, as the monetarista approach clearly puts it, with no intrinsic relevance. Secondly, we clarify the practical relevance that the quantity theory approach can bear in the twenty-first century. We argue that although the quantity theory is unsuitable to explain conventional monetary policies, the mechanism on which it builds bears relevance in analysing some recent unconventional monetary policies. Thirdly, we review the channels and assumptions underlying the asserted quantity theory link between money growth and inflation. In light of our analysis, we conclude that the high money growth rates seen since the pandemic outbreak are not likely to translate into higher inflation rates.